1986
DOI: 10.1159/000234024
|View full text |Cite
|
Sign up to set email alerts
|

Intraepithelial Migration of Nasal Mucosal Mast Cells in Hay Fever

Abstract: Mast cells were studied by light microscopy in mucosal imprints and in biopsies of nasal mucosa of 12 birch pollen allergic individuals before and during the pollen season, using techniques optimized for the demonstration of mucosal mast cells. We also measured the histamine content of nasal mucosa, whole blood and plasma, and counted the numbers of circulating blood basophils. Before the pollen season the nasal mucosa was found to contain many mast cells located in the mucosal connective tissue stroma, and ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
79
2

Year Published

1990
1990
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(91 citation statements)
references
References 10 publications
10
79
2
Order By: Relevance
“…The accumulation of mast cells takes place in relation to inflammatory conditions. 19,20) Oh et al reported that the number of mast cells in the nasal mucosa of AR mice was significantly higher than those in the OVA-unsensitized mice. 21) In the inflammatory process, proinflammatory cytokines recruit activated immune and inflammatory cells to the sites of lesions, thereby amplifying and perpetuating the inflammatory condition.…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of mast cells takes place in relation to inflammatory conditions. 19,20) Oh et al reported that the number of mast cells in the nasal mucosa of AR mice was significantly higher than those in the OVA-unsensitized mice. 21) In the inflammatory process, proinflammatory cytokines recruit activated immune and inflammatory cells to the sites of lesions, thereby amplifying and perpetuating the inflammatory condition.…”
Section: Discussionmentioning
confidence: 99%
“…With allergen exposure, mast cell migration to, and proliferation within, the epithelium occurs [67]. However, these epithelial mast cells predominantly express only tryptase (MC T ) and are selectively increased in AR [68][69][70]. Although SCF is a strong mast cell chemoattractant and elevated in the nasal lavage fluid of seasonal AR, relatively low levels of SCF are present in the nasal epithelium as compared with the lamina propria.…”
Section: Allergic Rhinitismentioning
confidence: 99%
“…Acidic Toluidine blue reveals the metachromatic property of MC by binding to sulfated glycosaminoglycans in the granules (Enerbäck et al, 1986;Markey et al, 1989). Some sections were stained with Alcian blue/safranin (AB/safranin); brain sections were first stained in 1% AB in 3% acetic acid (pH2.2) and followed by 0.5% safranin in HCl (pH1.3), according to a previously described technique (Chieffi Baccari et al, 1998).…”
Section: Histology and Histochemistrymentioning
confidence: 99%
“…Some sections were stained with Alcian blue/safranin (AB/safranin); brain sections were first stained in 1% AB in 3% acetic acid (pH2.2) and followed by 0.5% safranin in HCl (pH1.3), according to a previously described technique (Chieffi Baccari et al, 1998). The combination of these two dyes can distinguish granules containing low-sulfated glycosaminoglycans (AB-positive) from granules containing highsulfated glycosaminoglycans (safranin-positive) (Enerbäck et al, 1986;Markey et al, 1989).…”
Section: Histology and Histochemistrymentioning
confidence: 99%